1979
DOI: 10.1159/000241191
|View full text |Cite
|
Sign up to set email alerts
|

Light- and Electron-Microscopic Studies on the Gastric Parietal Cells in Perinatal Rats

Abstract: Perinatal changes of the gastric parietal cells were studied under normal and various experimental conditions. Histologic examination revealed that the parietal cells appeared markedly increased in number from late fetal to early neonatal days. When premature newborn rats were delivered by cesarean section and were nursed by foster mothers for 1 or 2 days, the degree of increase of these cells reached nearly that in the normal neonates. On the other hand, in fetuses retained in utero 1 day beyond the normal ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…On the other hand, immature parietal cells often contain dense granules resembling those in primitive chief cells in 2 week-old and younger mice in both the present study and in previous studies using mice (PIPAN, 1970) and rats (HELANDER, 1969a;MORIKAWA et al, 1979). A few immature parietal cells containing mucous granules were found in weaned and adult animals in this and previous studies (TAMURA andFUJITA, 1983, KATAOKA andSAKANO, 1984).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, immature parietal cells often contain dense granules resembling those in primitive chief cells in 2 week-old and younger mice in both the present study and in previous studies using mice (PIPAN, 1970) and rats (HELANDER, 1969a;MORIKAWA et al, 1979). A few immature parietal cells containing mucous granules were found in weaned and adult animals in this and previous studies (TAMURA andFUJITA, 1983, KATAOKA andSAKANO, 1984).…”
Section: Discussionsupporting
confidence: 82%
“…Some parietal cells exhibit a mature, fine structure with dilated secretory canaliculi, large round mitochondria and numerous tubulovesicular elements. MORIKAWA et al (1979) reported that the development of parietal cells was accelerated by oral administration of milk in both normal neonates and premature newborn rats delivered by cesarean section. The rapid, fine structural maturation of surface mucous and primitive chief cells that are demonstrated in the present study may also be caused by the intake of milk.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of milk in the functional development of parietal cells (Morikawa et al, 1979) and chief cells (Andren and Bjorck, 1986) has also been reported. Development of functional parietal cells in perinatal rats is accelerated by the administration of milk to foetuses in utero and premature newborn rats, whereas there is a delay in parietal cell development if parturition is delayed (Morikawa et al, 1979).…”
Section: Down-regulation Of Gastric-type Specialised Cells In the Formentioning
confidence: 97%
“…9], After birth, the parietal cells become functional and respond to ingested maternal milk by secret ing acid [10]. These findings lead us to think that Brunner's gland cells of newborn rats are Many secre tory granules are seen in the apical portion of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, main functions of the Brunner's glands are protection of the surface epithelium of the proximal duodenum from the damaging action of acid chyme ejected by the stomach [3][4][5][6] and lubrication to assist the onward movement of the chyme [3], Lang and Tansy [7] have reported that luminal acidifi cation of the proximal duodenum stimulates duodenal motility which in turn stimulates the secretion of mucus from the Brunner's glands. In fetal rats, gastric parietal cells se crete acid at least 1 or 2 days before birth [8,9], In perinatal rats, in addition, the number of parietal cells markedly increases from late fetal to early neonatal days, although the de gree of increase in these cells is accelerated to reach nearly that on neonatal days when some food material, such as milk, is introduced into the fetal stomach 2 days before birth (day 21 of gestation) and killed at the end of gestation (day 22 of gestation) [10]. Incidentally, the population of colonic goblet cells increases from fetal day 20 to neonatal day 2 with a striking increase between fetal day 22 and neonatal day 1 [11], The size of pancreatic acini also remarkably decreases after birth [12].…”
mentioning
confidence: 99%